VALUASI EKONOMI JASA LINGKUNGAN EKOSISTEM HUTAN TAMAN EDEN 100, DESA LUMBAN JULU, PARAPAT, SUMATERA UTARA - Ivany Gresya Saragih; Made Sudiana Mahendra; I Made Sudarma (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2019)
Eden 100 Forest Park is an ecotourism area that has the potential of natural resources that can be used as tourist attractions. Forest Park Eden 100 also provides environmental services such as hydrological forest services, forest services as carbon sinks, and forest services in producing timber and non-timber goods. This study aims to find out what environmental services are provided by the Eden 100 forest and to analyze the economic value of environmental services and the obstacles and challenges faced by managers in efforts to preserve forest ecosystems. The results showed that the Eden 100 Forest Park provides environmental services in the form of direct use environmental services, namely wood production with economic value of the economic value of wood production of Rp 7,822,633,800 and non-wood (fruits) of Rp 25,500,000, non-use value directly in the form of natural landscapes (ecotourism) whose value is calculated using the travel cost method (TCM) and a yield of Rp 1,164,181,800 is obtained, non-use value in the form of existence services whose economic value is calculated using the contingent valuation method (CVM) of Rp.60,158,120 , as a carbon sink value which is calculated using the allometric method, and a yield of Rp. 18,161,220,000 is obtained. From the results of this study, it can be concluded that the total economic value of the Eden 100 Forest is Rp. 27,233,693,720. This proves that the existence of the Eden 100 forest is a very big economic benefit if its sustainability is maintained because it can absorb carbon which gives a great economic value. Efforts to manage and preserve Eden Forest Park 100 as a tourist attraction have been carried out in an integrated manner with the government, private sector and local communities, but need to be increased so that forests can provide environmental services in a sustainable manner.